A comparative analysis of service quality in public and private sector hotels - Dogra, Twinkal (Journal of Tourism Management Research, 2023)
Service quality has been found to improve with trained staff, a proper customer feedback mechanism, and quick complaint resolution in business organisations. In India, people have a skewed perception of the efficiency of public sector service delivery as compared to private business organisations. The present study aims to investigate the impact of trained staff, proper customer feedback and quick complaint resolution on service quality in the public and private sector hotels. Research instruments such as questionnaires, personal interviews, and participatory observation were used to collect primary data from the respondents. The data were analyzed through the appropriate statistical tools by using Microsoft Excel ToolPak. Statistical tools such as the percentage method, cross tabulation, Chi-square test, independent sample t-test, one-way ANOVA, and Multiple Regression were used for the analysis. The findings reveal that Staff training, a proper feedback mechanism, and the resolution of customer complaints were essentially the indicators of good service quality in the hotel industry. The failure of the public sector organisations to properly address all three essential components of good service quality was a major factor in their inability to meet customer expectations.